Pengaruh Pemahaman Perpajakan, Efektivitas Sistem Perpajakan, dan Kualitas Pelayanan terhadap Kepatuhan Wajib Pajak - Rina Purnamasari; Sri Handayani (Universitas Sains dan Teknologi Komputer, 2023)
Tax payer compliance is a condition where taxpayers comply and have an awareness of fulfilling tax obligations. This study aims to find empirical evidence about the factors that influence taxpayer compliance. The factors tested in this study are the influence of understanding taxation, the effectiveness of the tax system, and the quality of service. The population in this study is individual taxpayers registered in the city of Tangerang with a total of 100 respondents. This sample was selected by accidental probability sampling. The data used in this study are primarily in the form of a questionnaire as an instrument in data collection, using the excel program and SPSS version 26. The data analysis used is a data quality test which includes validity and reliability testing, and the classic assumption test which includes normality, multicollinearity, heteroscedasticity, and autocorrelation tests. Hypothesis testing uses multiple linear regression techniques, simultaneous significance test (f-test), partial significant test (t-test), and coefficient of determination test (R2). The results of partial hypothesis testing prove that service quality has no significant effect on individual taxpayer compliance while understanding taxation and the effectiveness of the taxation system affect individual taxpayer compliance. Simultaneously understanding taxation, the effectiveness of the taxation system, and service quality have a positive and significant effect on individual taxpayer compliance with a determination coefficient of 49% while the remaining 51% is explained by other factors not examined.